Studi Kasus Dinamika Kognitif pada Proses Abstraksi dan Klasifikasi dalam Membangun Pemahaman Konseptual Geometri - Rosi Citrawati; Surya Sari Faradiba; M. Mahmudi Prasetiyo (Mandalika Mathematics and Educations Journal, 2026)
This research is motivated by the low spatial literacy among elementary school students, who tend to memorize physical features of shapes without understanding their hierarchical logical relationships. The primary objective is to deconstruct the cognitive dynamics in building geometric conceptual understanding through the integration of abstraction and classification processes. Adopting a descriptive qualitative case study design, the study included 5th-grade students selected via purposive sampling. Data were collected using the Conceptual Geometry Task instrument through the Think-Aloud Protocol (TAP) technique, observations, and task-based interviews, which were then qualitatively analyzed using data triangulation. Specific findings indicate that the subjects reached a mature stage of abstraction by extracting invariant attributes to perform hierarchical classification consistent with Van Hiele Level 1. Furthermore, a progressive self-correction mechanism was identified as a means of overcoming high cognitive load by modifying logical strategies. Contextually, this study indicates that students’ procedural errors are often integral to the process of developing conceptual abstraction. The practical implications emphasize the urgency for educators to validate students' learning trajectories to foster comprehensive mathematical reasoning.